Autofluorescent Imaging in Patients With Peritoneal Carcinomatosis. (April 2014) - von Breitenbuch, Philipp; Jeiter, Tonia; Schreml, Stephan; Glockzin, Gabriel; Agha, Ayman; Piso, Pompiliu; Schlitt, Hans J.
Background and objectives. Autofluorescence imaging (AFI) is mainly used to detect (pre)cancerous colorectal and pulmonal lesions. This is the first report establishing the feasibility of AFI in patients with peritoneal carcinomatosis (PC). Methods. This is a prospective analysis of 10 patients undergoing conventional white-light laparoscopy (WL) and AFI for PC of different gastrointestinal tumors and 1 ovarian cancer. Before taking biopsies, suspicious peritoneal lesions were first detected by WL and then investigated by AFI. The intraoperative findings were photographed and then correlated with histological results. Results. Conventional WL and AFI evaluation was successful in all patients. A total of 38 biopsies were taken. The neoplasm detection rate under WL was 66% and increased to 86% when using AFI. The positive tumor detection rate was slightly higher in low AF lesions (83 vs 88%) and higher in tumor nodules (94%) than in flat peritoneal lesions (75%). For tumor nodules, the sensitivity was 94%, and the specificity was 100%. For flat lesions, the sensitivity was 75% and specificity 50%. Conclusions. We demonstrate the feasibility and effectiveness of AFI in patients with PC.